ANALISA PERMINTAAN PARKIR DI STASIUN PONCOL DAN TAWANG SEMARANG - Sutarto, Agung (Semarang State University, 2010)
Abstract: Activities in a railway station will generate trips which need parking space. This research is aimed to analyze the difference demand characteristics between Poncol and Tawang stations. These characteristics are the effect of ticket price to trip attraction, trip attraction model, transportation mode demand and parking space demand. The economic class and transportation of goods are served in Poncol. Bussiness and executive class is served in Tawang stastion. The correlation between trip attraction and the number of ticket can be described in the following equation : Ytrip attraction = 120,51 + 1,0602 Xticket for Poncol station, and : Ytrip attraction = 175,21 + 1,3212 Xticket for Tawang station. Correlation between trip attraction and transportation mode can be described in the following equation : Ytripattr = 7,3063 + 3,271 Xprivate car + 2,464 Xbecak + 2,406 Xmotor cycle + 2,448 Xpick up for Poncol, and : Ytrip attraction = 4,467 + 3,567 Xprivate car + 2,517 Xmotorcycle, for Tawang station. It can be concluded that the parking space demand for each passenger is 1,48 m2 in Poncol station and 7,3 m2 in Tawang station. Trips attraction per ticket is 1,0602 in Poncol station and 1,3212 in Tawang station. Transportation mode which is dominantly used in Poncol station is motorcycle, while in Tawang station is private car and motorcycle. Private car is often used because the public transport facility could not support the train passenger’s needs. There are variable pick-up vehicles in Poncol because Poncol station served passengers and goods. SRP which are used in Poncol station for passenger car 65 SRP, motorcycle 282 SRP, pick-up 52 SRP, and tricycle (becak) 64 SRP. SRP which are used in Tawang station for passenger car 235 SRP, motor cycle 350 SRP and tricycle (becak) 13 SRP. Keywords: trips attraction, parking demand, poncol station, tawang station . Abstrak: Kegiatan di stasiun kereta api akan menghasilkan perjalanan yang membutuhkan ruang parkir. Penelitian ini bertujuan untuk menganalisis karakteristik permintaan perbedaan antara stasiun Poncol dan Tawang. Ciri ini pengaruh harga tiket ke atraksi perjalanan, model tarikan perjalanan, kebutuhan transportasi mode dan kebutuhan ruang parkir. Kelas ekonomi dan transportasi barang disajikan di Poncol.Bisnis dan kelas eksekutif disajikan di Tawang stastion. Korelasi antara daya tarik perjalanan dan jumlah tiket dapat digambarkan dalam persamaan berikut: Ytrip atraksi = 120,51 + 1,0602 Xticket untuk stasiun Poncol, dan: Ytrip atraksi = 175,21 + 1,3212 Xticket untuk stasiun Tawang. Korelasi antara daya tarik dan moda transportasi dapat digambarkan dalam persamaan berikut: Ytarikan = 7,3063 + 3271 Xmobil pribadi + 2.464 Xbecak + 2.406 Xsepeda motor + 2.448 Xpick-up untuk stasiun Poncol, dan: Ytarikan = 4467 + 3567 Xmobil pribadi + 2.517 Xsepeda motor, untuk stasiun Tawang. Dapat disimpulkan bahwa ruang parkir permintaan penumpang masing-masing 1,48 m² di stasiun Poncol dan 7,3 m² di stasiun Tawang. Perjalanan atraksi per tiket di stasiun Poncol 1,0602 dan 1,3212 di stasiun Tawang.Transportasi modus yang dominan digunakan di stasiun Poncol adalah sepeda motor, sedangkan di stasiun Tawang adalah mobil pribadi dan sepeda motor. mobil pribadi sering digunakan karena fasilitas transportasi publik tidak dapat mendukung kebutuhan penumpang kereta. Ada variabel kendaraan pick-up di stasiun Poncol Poncol karena melayani penumpang dan barang. SRP yang digunakan dalam stasiun Poncol untuk penumpang mobil 65 SRP, sepeda motor 282 SRP, pick-up 52 SRP, dan roda tiga (becak) 64 SRP. SRP yang digunakan dalam stasiun Tawang untuk mobil penumpang 235 SRP, sepeda motor 350 SRP dan roda tiga (becak) 13 SRP Kata kunci: bangkitan perjalanan, kebutuhan parkir, stasiun poncol, stasiun tawang